Mushaf Braille Elektronik: Perangkat Modern Dalam Pembelajaran Al-Qur’an Bagi Penyandang Disabilitas Tunanetra: Electronic Braille Qurans: A Modern Tool for Learning the Quran for the Blind - GUMAA AHMED HIMMAD; AHMAD BAHA BIN MOKHTAR; RIFQI HIDAYATIL (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
The development of technology and the progress of time have influenced various fields of education, including education and learning of the Quran for individuals with visual impairments. The Braille system of the Quran that based on raised dots on paper has been successfully converted by technology’s experts into a digital code to simplify access for the visually impaired in Quranic learning. This digitization is organized into a technological device called the Electronic Braille Qur’an, serving as a new medium currently being developed in several Islamic countries. This writing will conduct an exploration and preliminary introduction to the Electronic Braille Quran using a descriptive analytical method. The aim is to provide new information that can be considered as an option or alternative in Quranic learning for individuals with visual impairments. Research findings indicate that there are currently two electronic Braille Qurans being developed in Islamic countries, the EBraille Quran and the EBraille Haramain Quran. Both devices are portable and store a digital database of Braille code for the Quran. They are designed to assist the role of the print version of the Braille Quran, which is not yet user-friendly for individuals with visual impairments. Each of these Braille Qurans has its own advantages and strengths. However, the use of EBraille Haramain is more suitable for simply reading the Quran due to its smaller and more portable size. On the other hand, the EBraille Quran is more suitable for the teaching and learning process as it is supported by a system that facilitates interaction and communication between teachers and students.